H4K5 Butyrylation Coexist with Acetylation during Human Spermiogenesis and Are Retained in the Mature Sperm Chromatin - de la Iglesia, Alberto; Jauregi, Paula; Jodar, Meritxell; Barrachina, Ferran; Ded, Lukas; Mallofré, Carme; Rodríguez-Carunchio, Leonardo; Corral, Juan Manuel; Ballescà, Josep Lluís; Komrskova, Katerina; Castillo, Judit; Oliva, Rafael (International journal of molecular sciences, 2022)
Male germ cells experience a drastic chromatin remodeling through the nucleo-histone to nucleo-protamine (NH-NP) transition necessary for proper sperm functionality. Post-translational modifications (PTMs) of H4 Lys5, such as acetylation (H4K5ac), play a crucial role in epigenetic control of nucleosome disassembly facilitating protamine incorporation into paternal DNA. It has been shown that butyrylation on the same residue (H4K5bu) participates in temporal regulation of NH-NP transition in mice, delaying the bromodomain testis specific protein (BRDT)-dependent nucleosome disassembly and potentially marking retained nucleosomes. However, no information was available so far on this modification in human sperm. Here, we report a dual behavior of H4K5bu and H4K5ac in human normal spermatogenesis, suggesting a specific role of H4K5bu during spermatid elongation, coexisting with H4K5ac although with different starting points. This pattern is stable under different testicular pathologies, suggesting a highly conserved function of these modifications. Despite a drastic decrease of both PTMs in condensed spermatids, they are retained in ejaculated sperm, with 30% of non-colocalizing nucleosome clusters, which could reflect differential paternal genome retention. Whereas no apparent effect of these PTMs was observed associated with sperm quality, their presence in mature sperm could entail a potential role in the zygote.
Keywords: epigenetic regulation; Acetylation; Humans; Chromatin; Histones; sperm chromatin; restrukturace chromatinu; Mice; zvířata; Nucleosomes; Spermatozoa; Protein Processing, Post-Translational; Spermatids; spermatidy; Spermatogenesis; histony; spermatogenesis; mužské pohlaví; Protamines; posttranslační úpravy proteinů; butyrylation; spermatogeneze; myši; H4K5; chromatin; sperma; Animals; lidé; protaminy; acetylation; acetylace; Semen; spermie; Male; sperm; nukleozomy; Chromatin Assembly and Disassembly